2017
DOI: 10.3390/en10122161
|View full text |Cite
|
Sign up to set email alerts
|

Battery Storage Systems as Grid-Balancing Measure in Low-Voltage Distribution Grids with Distributed Generation

Abstract: Due to the promoted integration of renewable sources, a further growth of strongly transient, distributed generation is expected. Thus, the existing electrical grid may reach its physical limits. To counteract this, and to fully exploit the viable potential of renewables, grid-balancing measures are crucial. In this work, battery storage systems are embedded in a grid simulation to evaluate their potential for grid balancing. The overall setup is based on a real, low-voltage distribution grid topology, real sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Adding battery storage to a residential grid smoothens the power characteristics by reducing the peak to average ratio. However, in [162], it is found that voltage quality is not significantly affected.…”
Section: Grid Structure and Operational Aspectsmentioning
confidence: 93%
“…Adding battery storage to a residential grid smoothens the power characteristics by reducing the peak to average ratio. However, in [162], it is found that voltage quality is not significantly affected.…”
Section: Grid Structure and Operational Aspectsmentioning
confidence: 93%
“…One of the ways to increase the efficiency of using solar installations is to use energy storage technologies, which make it possible to distribute electricity generated from solar power plants during the day (Figure 7) [38,[59][60][61]. generation.…”
Section: Empirical Model: a Case Study Of Krasnodar Region Of Russiamentioning
confidence: 99%
“…Ali et al discussed the issue of minimizing energy losses through finding the optimal size and location of renewable energy sources and battery storage units using a mixed integer Genetic Algorithm (GA) optimization approach. Faessler et al evaluated the potential of battery storage systems in grid balancing based on different battery locations and incentives. The analysis demonstrated that central energy storage lead to better performance in terms of minimizing the voltage drop/rise and distribution losses.…”
Section: Introductionmentioning
confidence: 99%